A Literatur Review of Turover Intention : Antecedents and the Outcomes - Siregar, Zulkifli Musannip Efendi; Azmi, Nurul (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2024)
Desire to find a new job in the same field in another company. Seeing another company that is felt to be able to provide more profits than the place where he currently works can be the main reason for an individual to trigger his desire to leave the company. However, this will be limited as he will only accept if it suits his current skills